1969
DOI: 10.1002/lipi.19690710815
|View full text |Cite
|
Sign up to set email alerts
|

Zur Polarographie von Peroxiden im Null‐Volt‐Bereich II: Oszillopolarogramme von Hydroperoxiden, Quecksilbersalzen und Hg‐Ionen in Gegenwart von Diacylperoxiden

Abstract: tion contains mainly of the di-succinyl and monocyclohexenyl adduct with a very small percentage of the mono-succinyl and mono-cyclohexenyl adduct, which are formed by Diels-Alder reaction of the conjugated mono-succinyl adduct with another mole of maleic anhydride. The molecular weight confirmed this.In order to identify the cyclohexene-structure, the esterified adduct was dehydrogenated into an aromatic structure. Ultraviolet spectra showed maxima at 273 mp and a shoulder a t 281 mp due to substituted benzen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1972
1972
1972
1972

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…In other studies with aromatic Schiff bases, correlations were found with IR spectra, Hueckel calculations, and Hammett values (71). The effect of substituents was considered in studies with XC6H|N=CHCeH4Y derivatives (188).…”
Section: Aldehydesmentioning
confidence: 99%
See 1 more Smart Citation
“…In other studies with aromatic Schiff bases, correlations were found with IR spectra, Hueckel calculations, and Hammett values (71). The effect of substituents was considered in studies with XC6H|N=CHCeH4Y derivatives (188).…”
Section: Aldehydesmentioning
confidence: 99%
“…Several books related to the topics of this review have been published in English or translated into English. The textbook on electrochemistry by Koryta, Dvorak, and Bohackova, which was first published in Czechoslovakia in 1966, can now be read in English (188).…”
Section: Thismentioning
confidence: 99%